2019
DOI: 10.2147/cmar.s210004
|View full text |Cite
|
Sign up to set email alerts
|

<p>Correlation of NRF2 and progesterone receptor and its effects on ovarian cancer biology</p>

Abstract: Purpose: This study aimed to investigate the potential prognostic impact of nuclear factor erythroid 2-related factor 2 (NRF2) and progesterone receptor A (PRA)/progesterone receptor B (PRB) in ovarian cancer patients which might be the rationale for putative new treatment strategies. Patients and methods: The presence of NRF2 and PRA/PRB was investigated in 156 ovarian cancer samples using immunohistochemistry (IHC). Staining of NRF2 and PRA/ PRB was rated using the semi-quantitative immunoreactive score (IR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…AKR1C1 belongs to the aldo-keto reductase (AKR) superfamily of nicotinamide adenine dinucleotide phosphate (NADPH)-dependent oxidoreductases [48,49] and has a major role in progesterone metabolism [40,47,50]. Moreover, AKR1C1 can bind to the promoter region of the progesterone receptor and hereby decreases receptor activity [51]. AKR1C1 is expressed ubiquitously [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…AKR1C1 belongs to the aldo-keto reductase (AKR) superfamily of nicotinamide adenine dinucleotide phosphate (NADPH)-dependent oxidoreductases [48,49] and has a major role in progesterone metabolism [40,47,50]. Moreover, AKR1C1 can bind to the promoter region of the progesterone receptor and hereby decreases receptor activity [51]. AKR1C1 is expressed ubiquitously [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…A clinical study has indicated that high cytoplasmic Nrf2 expression (the inactivated form of Nrf2 ) in serous carcinoma subtypes is associated with longer survival (p < 0.05), which appears to correlate with high ERα expression (p < 0.05) [ 42 ]. The same team found that Nrf2 expression in the cytoplasm was positively correlated with PR expression (p < 0.05) [ 43 ]. Furthermore, a retrospective study of the relationship between Nrf2 expression and clinical prognosis in 108 patients with different subtypes of OC showed that a high expression of Nrf2 in OC indicates short DFS (HR: 2.084; 95% CI: 1.229–3.536) and OS (HR: 2.487; 95% CI: 1.443–4.286) [ 44 ].…”
Section: Nrf2 Regulation In Ocmentioning
confidence: 99%
“…Chen et al argued that knockdown of Nrf2 in the SKVO3 cell line increased the production of ROS induced by cisplatin by increasing the phosphorylation level of p38-JNK .This subsequently led to elevation of ATF2 levels, followed by decreased expression of AKR1C1 ,which is involved in apoptosis, ultimately promoting the sensitivity of OC to cisplatin [ 53 ]. It was recently reported that activation of Nrf2 promotes activation of its downstream gene AKR1C1 , which converts progesterone to an inactive form and promotes platinum resistance in ovarian cancer, while metformin reverses this process by increasing PR expression [ 54 ]. Mechanistically, Sun et al found that SIRT5 contributes to the cisplatin resistance of OC by inhibiting cisplatin-mediated DNA damage via ROS through Nrf2 pathway modulation [ 55 ].…”
Section: Effect Of Nrf2 On Treatments For Ocmentioning
confidence: 99%
“…Studies have indicated that NRF2 is mainly regulated by Keap1 [31], and that NRF2 plays an important role in regulating ovarian dysfunction and treating ovarian cancer [32][33][34][35]. Further studies have clarify that SESN2 could both directly and indirectly participate in the regulation of NRF2 in the process of metabolism [19,36].…”
Section: Introductionmentioning
confidence: 98%